A fragment of a Pictish symbol-bearing slab with carving in relief from Mail, Cunningsburgh, Shetland - Ritchie, Anna (Proceedings of the Society of Antiquaries of Scotland, 2009)
A fragment of carved stone found in March 2008 is considered likely to be part of a Pictish cross-slab of eighth- to tenth-century date. It bears a double disc and Z-rod within a frame and part of an interlace design, carved in incision and low relief. This is the fifth symbol-bearing monument known from Shetland and the only one to bear this particular symbol. Each disc is infilled with a cross of arcs, but it is uncertain whether this is purely decoration or whether it has Christian meaning.